ANALISIS PENGARUH RELATIONSHIP CONFLICT TERHADAP MOTIVASI KERJA KARYAWAN DI UNIVERSITAS MUHAMMADIYAH SURAKARTA - Hakim, Lukman; Irawati, Zulfa (Universitas Muhammadiyah Surakarta, 2011)
The research examined the impact relation conflict with the setting of high shool institution namely the University Muhammadiyah of Surakarta. The objective was to analyze whether the variable of worker behavioral attributes model of relation conflict consisting of miscommunication, naïve realism, intervence, faulty attribution, disagreement and negative emotion significantly affecting the work motivation. The sampling as many as 48 persons was taken by using purposive method. They comprised the managers whose qualifications were as workers of administration unit in university. From the 48 persons taken as samples through questioner sheets, 40 questioner sheets were returned but one of them was damaged. Therefore, there were only 38 questioner sheets which were valid to be analyzed. The result of regression analysis by using the instrument called the program SPSS showed that miscommunication and negative emotion significantly negative affecting the work of motivation. The naïve realism has effect positively significant toward work of motivation. Whereas the others variable such as naive realism, intervence, faulty attribution, disagreement have not effect negatively significant toward the work of motivation.